Dermatomiosite juvenil associada a anasarca - a propósito de um caso clínico - Mourão, A F (2009)
Acta Reumatol. Port. Mourao, Ana Filipa Pinto, Teresa Laura Falcao, Sandra Ribeiro, Celia Vieira, Helena Caetano-Lopes, Joana Nero, Patricia dos Santos, Fernando Pimentel Guimaraes, Jose Branco, Jaime Cunha21 MEDFARMA-EDICOES MEDICAS, LDA ALGES 447VL